The Implementation of Operational Risk Management for Reducing the Risk Priority Number in the Metalworking Company - Ega Rizkiyah; Dewi, Ratna Sari Dewi; Maryani, Anny Maryani; Rizkiyah, Ega Rizkiyah; Prakoso, Indrayadi Dwi Prakoso (Jurusan Teknik Industri, Fakultas Teknologi Indusri Universitas Trisakti, 2024)
There were 47 work accidents at the studied manufacturing company from 2014 to 2016. Thehighest number of work accidents occurred in metalworking processes such as forging and casting,where as many as 22 work accidents, or 46.8% of the total number of work accidents, occurred. So itis necessary to identify the causes of work accidents and control the risk of operational workaccidents. Accidents that occur include being squeezed, bumped, run over, punctured, cut, scratched,hit by an explosion, involved in traffic accidents, and others. So this study aims to prevent these typesof accidents. This study applied hierarchical risk control methodology to provide risk control andreduce the Risk Priority Number (RPN) value for each work activity that has the highest number ofwork accidents. Recommendations that can be implemented are engineering control, administrativecontrol, and PPE control for melting, furan, disamatic, fettling/clearing, and finishing workstations.The results of the proposed risk control resulted in a decrease in the RPN at each workstation.